Supraglottic Carcinoma in Intravenous Opioid Drug Abusers: A Distinct Disease with Improved Survival. (18th September 2020) - Yaniv, Dan; Reuven, Yonatan; Lahav, Yonatan; Cohen, Oded; Hamzany, Yaniv; Moore, Assaf; Rapana, Olga G.; Argaman, Natan; Halperin, Doron; Popovtzer, Aron; Bachar, Gideon; Shoffel‐Havakuk, Hagit
Abstract : Objectives/Hypothesis: Recent evidence indicates an increased prevalence of intravenous opioid drug abusers (IVDAs) among supraglottic squamous cell carcinoma (SG‐SCC) patients. This study investigates whether the clinical course of SG‐SCC in IVDA differs from SG‐SCC in non‐IVDA. Study Design: A retrospective case–control study conducted in a in two tertiary referral centers. Methods: This case–control study compares IVDA with non‐IVDA patients diagnosed and treated for SG‐SCC in between 2005 and 2018. Disease‐free survival (DFS) and overall survival (OS) were calculated using the Kaplan–Meier estimator. Adjusted odds ratios (ORs) for mortality were calculated using multivariant analyses. Results: A total of 124 patients were included; 21% (26) were IVDA, and 79% (98) were non‐IVDA. Age at diagnosis in the IVDA group versus the non‐IVDA group was 53 and 66 years, respectively ( P = .001). Nevertheless, the age hazard ratio for OS was calculated and found to have minimal to no effect, 1.05 (95% Cl: 1.025–1.076). Otherwise, the two groups were comparable regarding demographics, other risk factors (i.e., gender, smoking, and alcohol), and comorbidities status, as well as the comparable stage at diagnosis, histologic grading, and treatment modalities. Although the DFS was comparable in both groups, the 5‐year OS was 55% in the IVDA group compared with 34% among the non‐IVDA patients ( P = .04). In multivariant analyses for mortality, positive IVDA history was found to be protective, adjusted OR: 0.263 (95% CI: 0.081–0.854). Similarly, within the subgroup of 100 patients with advanced‐stage disease (III and IV), the adjusted OR was 0.118 (95% CI: 0.028–0.495). Conclusions: SG‐SCC in IVDA patients has a distinct clinical course, presenting at a younger age, and may have improved prognosis. Level of Evidence: NA Laryngoscope, 131:E1190–E1197, 2021